1998
DOI: 10.1191/026921698673226380
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus infection in palliative care

Abstract: Our objective was to assess the impact of methicillin-resistant Staphylococcus aureus (MRSA) infection in palliative care. The study was conducted at three hospices in south London, totalling 118 beds, and the following two methods were used. Firstly, a retrospective review of the notes of patients who were known to be MRSA positive at admission or were subsequently found to be MRSA positive was taken. Secondly, a prospective study of factors influencing bed occupancy in one hospice was conducted. The proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 11 publications
0
21
0
1
Order By: Relevance
“…19,20 A North American cohort study raised the concern of inferior care of isolated patients, 21 and two observational studies from the US recorded significantly less health care provider/ patient contact in isolated than in non-isolated patients. 22,23 The results of our global assessment of current MRSA containment policies in German palliative care institutions do add evidence from a professional caregivers' and institutional perspective to the cross-border notion of negative effects of such policies on patients both in the palliative care 5,7,8 and in other settings. 1,2,18 Next steps should begin with conducting a multi-centre mixed-method investigation of affected patients' and relatives' opinions on their experience of the MRSA regimen to estimate the magnitude of the problem within the palliative care settings.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…19,20 A North American cohort study raised the concern of inferior care of isolated patients, 21 and two observational studies from the US recorded significantly less health care provider/ patient contact in isolated than in non-isolated patients. 22,23 The results of our global assessment of current MRSA containment policies in German palliative care institutions do add evidence from a professional caregivers' and institutional perspective to the cross-border notion of negative effects of such policies on patients both in the palliative care 5,7,8 and in other settings. 1,2,18 Next steps should begin with conducting a multi-centre mixed-method investigation of affected patients' and relatives' opinions on their experience of the MRSA regimen to estimate the magnitude of the problem within the palliative care settings.…”
Section: Discussionmentioning
confidence: 95%
“…Of three studies, one observed a colonization prevalence of 4-8% in a retrospective chart review of three different hospices in London. 7 Another group surveyed a single hospice -also in London -using an observational design. They found that 9.2% of patients admitted from settings with unknown MRSA presence had MRSApositive swabs at some point during their hospice stay, while 7.1% from wards with known MRSA background tested positive.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, patients with malignancy have a high risk of MRSA infection. Cancer chemotherapy may induce an immunosuppressed condition; radiotherapy often elicits local inflammation, especially mucitis; and surgery breaks local barriers against pathogens and could cause MRSA wound infection [8,9]. Of the 318 consecutive patients with head and neck cancers in the present study, about 14% were positive for MRSA.…”
Section: Discussionmentioning
confidence: 96%
“…Tal vez, la edad avanzada en la comunidad y la mayor importación de ancianos, colonizados o portadores de cepas resistentes, que son trasladados entre hospitales o centros de larga estancia sean los principales motivos, como han sugerido algunos autores (19,20). En cuanto al predominio estival de infección observado por A. baumanii, se conoce que su tasa de incidencia es al menos dos veces mayor al final del verano que en invierno (21).…”
Section: Discussionunclassified